The Influence of Islamic Spirituality on Teaching Professionalism among Islamic Religious Education Students at the Institute Ahmad Dahlan Probolinggo - Rizal Setiawan; Abdul Muhaimin Akhamadi; Benny Prasetiya (Education Reserach Center, 2026)
This study aims to analyze the influence of Islamic spirituality on teaching professionalism among students of the Islamic Religious Education Study Program at the Ahmad Dahlan Institute of Probolinggo. The research employs a quantitative approach with an explanatory research design to examine the relationship between Islamic spirituality as the independent variable and teaching professionalism as the dependent variable. The population consists of all students of the Islamic Religious Education Study Program. The sampling technique used is probability sampling through the simple random sampling method. Data collection is conducted using a questionnaire developed based on indicators of Islamic spirituality and teaching professionalism, measured using a Likert scale. The collected data are analyzed using descriptive statistical analysis and simple linear regression to test the research hypothesis. The results show that Islamic spirituality has a positive and significant influence on students’ teaching professionalism. Students with higher levels of spirituality tend to demonstrate stronger commitment to academic responsibilities, greater awareness of professional ethics, and higher readiness to develop pedagogical competencies. These findings indicate that Islamic spirituality functions not only as a personal religious dimension but also as a moral and motivational foundation in shaping the professionalism of prospective educators. Therefore, strengthening spiritual values in higher education, particularly within the Islamic Religious Education Study Program, is essential to develop professional teachers with integrity and strong Islamic character.